Hypersensitivity pneumonitis related to imatinib mesylate therapy in a patient with chronic myeloid leukemia. (October 2021) - Kallel, Faten; Kassar, Olfa; Maaloul, Imen; Charfi, Maha; Ksouda, Kamilia; Elloumi, Moez
Introduction: Pulmonary toxicity causally related to Imatinib (IM) therapy is uncommon in patients with chronic myeloid leukemia. Case report: A 61-year-old patient with chronic myeloid leukemia was treated with IM at 400 mg daily dose. One month within IM, he developed skin lesions and then acute dyspnea and non-productive cough. Chest radiograph and high-resolution lung computed tomography (CT) revealed bilateral reticulonodular infiltration in both lungs. According to Naranjo's algorithm, the causality relationship with the drug is probable with a score of 7. The pharmacovigilance investigation was carried out and implicated IM Management & outcome: IM was discontinued and started steroid therapy (Prednisolone®) at 1 mg/kg daily. Two weeks after, the dyspnea, and abnormal X-ray and CT findings are improved. Discussion: The early diagnosis of pulmonary toxicity related to IM therapy is needed to avoid further determinal effects of the drug.